Collaborative convergence and virtual teamwork for organizational transformation - Zhao, Jingyuan 1968- (IGI Global, Publisher of Timely Knowledge, 2021)
"This book addresses the design and implementation of e-collaboration technologies, and their use in business today establishing the important links between the use of e-collaboration technologies and behavioral patterns in the workplace" - Provided by publisher
Keywords: Organizational change; Virtual work teams; Communication / Technological innovations; Business enterprises / Computer networks; Aufsatzsammlung